HIDRADENITIS SUPPURATIVA: A RETROSPECTIVE REVIEW OF 13 PATIENTS AND LITERATURE SUMMARY - Reneeka Persaud; James A. Elliott; Laurie Goodman; Ranjani Somayaji; Morgan Lim; Gary Sibbald (European Medical Journal Dermatology, 2017)
Hidradenitis suppurativa (HS) is an inflammatory skin condition of the follicular pilosebaceous unit that primarily affects flexural areas where apocrine glands are found. This disorder can present as either an acute or chronic disease, with a single subcutaneous nodule or clusters of painful abscesses with purulent drainage in one or more of the following sites: axilla, groin, genital, perianal (more common in males), and under the breasts (more common in females). Over time patients form sinus tracts, fibrosis, and scarring. The onset usually occurs in the early 20s, after puberty. HS can be present for years without being diagnosed and is associated with a diminished quality of life, high morbidity, and substantial healthcare costs. Global HS prevalence is estimated at 1%.